Quality of spray-dried pitaya fruit powder as natural colourant. - Ng, L. T.; Han, C. P.; Yusof, Yus Aniza; Chin, Nyuk Ling; A. Talib, Rosnita; Aziz, Mohammad Gulzarul (2012)
In this study natural colourant from whole pitaya fruit was produced by spray drying using two concentrations of maltodextrin 20% and 30% and four different inlet temperatures from 1450C to 1750C and quality of powder in terms of physico-chemical and nutritional properties were investigated. The best spray drying condition in relation to betacyanin content was 1550C inlet temperature and 20% maltodextrin concentration. From the flowability analyses, the powders showed poor flowing characteristics. In terms of nutritional qualities, pitaya fruit powder was found rich in protein, fat, ash, fiber and antioxidant. This findings show that the pitaya fruit powder produced from whole pitaya fruit has potential to be used as natural colouring agent and a health supplement.